Treatment of cervical artery dissection: a systematic review and meta-analysis. Issue 10 (26th February 2008) - Menon, R; Kerry, S; Norris, J W; Markus, H S
Abstract : Background and purpose: Cervical dissection is an important cause of stroke in the young. This paper presents a systematic review and a meta-analysis to assess the effectiveness of different treatment approaches: antithrombotic drugs, thrombolysis and stenting. Methods: Medline and PubMed were searched from 1966 to 8 April 2007. Reference lists were reviewed. Separate searches were performed for treatment with anticoagulation and antiplatelet therapy during the acute phase (within 1 month of symptoms), thrombolysis and stenting. Results: There were only sufficient data for meta-analysis for the comparison of antiplatelet versus anticoagulation therapy. No randomised trials were identified. 34 non-randomised studies included 762 patients. There was no significant difference in risk of death (antiplatelet 5/268 (1.8%), anticoagulation 9/494 (1.8%), p = 0.88); stroke (antiplatelet 5/268 (1.9%), anticoagulant 10/494 (2.0%), p = 0.66), or stroke and death. Four non-randomised studies of thrombolysis provided insufficient data for assessment of efficacy but complication rates were no greater than thrombolysis for other ischaemic stroke. Six studies included 96 patients undergoing stenting for both acute dissection and chronic complications, providing insufficient data for assessment of efficacy, although complication rates appeared similar to those published for carotid atherosclerosic stenosis. Conclusions: There are no data to support the therapeutic superiority of anticoagulants over antiplatelet agents. Thrombolysis in dissection appears safe but more data on efficacy are required. Stenting is technically possible but there are no data to demonstrate efficacy. There is little evidence to support current treatment approaches in cervical dissection. Randomised controlled prospective trials, particularly assessing anticoagulation versus antiplatelet agents, are required.